The application of medical scale in the treatment of plantar warts: analysis and prospect. (17th February 2022) - Huang, Kai; Li, Mingjia; Xiao, Yi; Wu, Lisha; Li, Yixin; Yang, Yang; Shi, Guanzhong; Yu, Nianzhou; Liu, Dihui; Su, Juan; Wang, Xianggui; Zhao, Shuang; et al.
Abstract: Plantar warts are common cutaneous diseases on the sole caused by the human papillomavirus, with a high annual incidence rate of 14%. It often causes pain, which impairs quality of life of patients. Numerous therapeutic options for plantar warts exist with variable success. However, all of them, including first-line treatment, have different adverse reactions or high recurrence rates. There is no one effective method for all patients. The choice of treatment method puzzles doctors. With the help of medical scales, we can analyze the patients' condition, so as to guide the choice of treatment methods, which is of great significance for the individualized treatment of patients with plantar warts. This review takes cryotherapy, intralesional injection of bleomycin and photodynamic therapy as examples to discuss the application of medical scales in the treatment of plantar warts, summarizes the scales that can be used to evaluate the status of plantar wart, adverse reactions, prognosis and patient's financial situation, and discusses their clinical and scientific value. We hope to use scales to consider the severity of plantar warts and economic level, help different patients to choose different treatment options, and make suggestions on the evaluation of the adverse reactions and treatment effect.